The Influence of Student Personality Behavior and Organizational Leadership on Self-Deflopment and Self-Efficacy as Mediator: PLS-SEM Analysis - Sulaiman Abdul Rasid; fadli, M. Fadli Al Azhari; Wafiq, Wafiq Aisyah Pratiwi (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2025)
One organization that plays a significant role in shaping the identity and development of migrant students is the Association of Indragiri Hilir Students (IPMI) Ponorogo. This association unites students from Indragiri Hilir studying in Ponorogo, providing a platform for solidarity, leadership, and cultural preservation. This study aims to examine the influence of students’ personality culture and organizational leadership on self-development and its impact on self-efficacy. The research involved 48 active members of the Indragiri Hilir Student Association (IPMI) in Ponorogo, using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results revealed that organizational leadership significantly influenced self-development (β = 0.708; p = 0.002), whereas personality culture had no significant effect on either self-development (β = 0.155; p = 0.503) or self-efficacy (β = 0.300; p = 0.294). Self-development had a strong and significant effect on self-efficacy (β = 0.679; p = 0.001). Additionally, self-development significantly mediated the effect of organizational leadership on self-efficacy (β = 0.480; p = 0.009), but not the effect of personality culture (β = 0.105; p = 0.571). The model’s explanatory power was high, with R² values of 72.9% for self-development and 72.0% for self-efficacy. These findings highlight the critical role of organizational leadership in fostering students' personal growth and confidence.